Hubungan Jarak Kehamilan dan Paritas dengan Kejadian Berat Bayi Lahir Rendah (BBLR) di RSUD Embung Fatimah Kota Batam - Nelli Roza; Andi Wilda Arianggara; Ayu Rosanti Wilujeng; Susi Endriani; Tetiana Randhanie (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2020)
Low birth weight infant are an important indicator for the reduction of Infant Mortality Rate and more than 95% of low birth weight infant is born in developing countries. Aware of data from Dinas Kesehatan Batam, low birth weight infant is the leading cause of death in infant. Even parity and non-optimal pregnancy spacing are the main factors in the occurrence of low birth weight infant. This study aims to determine the relationship between parity and distance of pregnancy with the incidence of low birth weight infant at RSUD Embung Fatimah Batam City. This study used a retrospective cohort research design using secondary data in the medical record section of RSUD Embung Fatimah Batam City. The study population was childbirth mothers, observed to assess whether the babies were born low or normal birth weight. The data analysis used in this study was univariable (descriptive), bivariable (chi-square), multivariable and (multiple logistic regression modeling). Stratification Test. The results of the analysis showed a significant relationship between parity and distance of pregnancy with the incidence of low birth weight infant. Mothers with at-risk parity were 4.565 times more likely to cause birth weight and 4.565 times more likely to have birth weight than mothers with non-risk parity (RR: 4.565, 95% CI, p-value 0.01 p<0.05). And mothers with a pregnancy gap of <36 or > 60 months were 2.556 times more likely to give birth to babies with low birth weight compared to mothers with a gestational gap of 36-60 months (RR: 4.556, 95% CI, p-value 0.01 p <0.05). So it can be concluded that parity and spacing of pregnancy have a significant relationship with the incidence of low birth weight infant.